Tailoring the Nucleation of Domain Walls Along Multi-Segmented Cylindrical Nanoelements - Altbir-Drullinsky, D; Allende-Prieto, S (Institute of Physics Publishing, 2015)
The magnetization reversal of three-segment cylindrical nanoelements comprising alternating nanowire and nanotube sections is investigated by means of Monte Carlo simulations. Such nanoelements may feature a three-state behaviour with an intermediate plateau in the hysteresis curve due to a metastable pinning of the domain walls (DWs) at the wire-tube interfaces. It turns out that vortex as well as transverse DWs contribute to the magnetization reversal. By varying the geometric parameters, the sequence, or the material of the elements the nucleation location of DWs, as well as their nucleation field, can be tailored. Especially interesting is the novel possibility to drive DWs coherently in the same or in opposite directions by changing the geometry of the hybrid nanoelement. This important feature provides additional flexibility to the construction of logical devices based on DW movement. Another prominent outcome is that DWs can be nucleated near the centre of the element and then traverse to the outer tips of the cylindrical structure when the applied field is increased, which also opens the possibility to use these three-segment nanoelements for the field-induced delivery of DWs as substitutes for large nucleation pads. © 2015 IOP Publishing Ltd.